The Influence of Organizational Leadership and Coaches on Indonesian Athletes' Adversity Quotient (Intelligence) - Diny Atrizka; Ikbar Pratama, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
The primary purpose of this study was to examine the relationship between adversity quotient and trust in coaches, self-efficacy of coaches, team emotional intelligence, and leadership. This study also assessed the mediatory function of leadership. Using convenience sampling, data were obtained from the athletes of Indonesian sports teams for this purpose. The information was gathered using questionnaires adapted from previous studies. The study's usable response rate was 61.80 percent. Leadership favorably affects the adversity quotient, according to the study's results. Additionally, effectiveness, trust in coaches, and emotional intelligence have a favorable impact on leadership. Further, the leadership's mediation impact is also supported. The study's findings will aid academics in their future research endeavors.